2019
DOI: 10.15294/biosaintifika.v11i2.20018
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Antiglycation Activity of Rhizosphere and Endophytic Actinobacteria of Xylocarpus granatum

Abstract: Utilization of endophytic bacteria such as actinobacteria is one of the alternatives to obtain the bioactive compounds similar to the host plant. This study aimed to identify compounds produced by rhizosphere and endophytic actinobacteria isolated from Xylocarpus granatum for their antioxidant and antiglycation activity. Actinobacterial culture supernatant was extracted using ethyl acetate with a ratio of 1:1 (v/v). Antioxidant activity was performed using 2,2-diphenyl-1-picrylhydrazyl (DPPH). Whole TLC-bioaut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…Determination of Antiglycation Activity Antiglycation activity was analyzed by method that described previously (Ariansyah, Batubara, Lestari, & Egra, 2019). The extract was dissolved in distilled water and made to a concentration of 1.0 mg/mL.…”
Section: %Inhibition =[mentioning
confidence: 99%
“…Determination of Antiglycation Activity Antiglycation activity was analyzed by method that described previously (Ariansyah, Batubara, Lestari, & Egra, 2019). The extract was dissolved in distilled water and made to a concentration of 1.0 mg/mL.…”
Section: %Inhibition =[mentioning
confidence: 99%
“…In recent, there have been several studies of antioxidant activity in actinobacteria in Indonesia, including the antioxidant activity of endophytic actinobacteria in mangosteen peel (Larasati et al 2020), Xylocarpus granatum (Ariansyah et al 2019;Ratte et al 2022), Eleutherine palmifolia (Shabira et al 2022). In addition, the study of pigmented bacteria has also been reported, including bacteria found in seaweed Kappahycus alvarezii (Arlita et al 2013), mangrove sediment bacteria (Riyanti et al 2019), and marine bacteria (Abubakar et al 2022).…”
mentioning
confidence: 99%